1988
DOI: 10.1073/pnas.85.23.9194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations and variations of HLA-A2 on recognition of a virus peptide epitope by cytotoxic T lymphocytes.

Abstract: Cytotoxic T lymphocytes (CTL) specific for influenza A virus were prepared from 15 donors. Those with HLA-A2 recognized autologous or HLA-A2-matched Blymphoblastoid cells in the presence of synthetic peptide representing residues 55-73 or 56-68 of the virus matrix protein sequence. Influenza A virus-specific CTL from donors without HLA-A2 or with an HLA-A2 variant type failed to respond to this peptide. CTL lines specific for HLA-A2 plus peptide did not lyse peptide-treated target cells from HLA-A2 variant don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
1

Year Published

1989
1989
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 27 publications
3
62
1
Order By: Relevance
“…Class I HLA molecules are involved in T cell-mediated cytotoxicity against virally infected cells as restriction molecules and it has been shown that not all class I antigens are recognized equally by cytotoxic T lymphocytes specific for different virus antigens [23,24]. These observations, explained by the molecular structure of class I HLA antigens [25] suggest that our findings are due to a different ability for antigen presentation by B51 + and B52+ lymphocytes.…”
Section: Discussioncontrasting
confidence: 38%
“…Class I HLA molecules are involved in T cell-mediated cytotoxicity against virally infected cells as restriction molecules and it has been shown that not all class I antigens are recognized equally by cytotoxic T lymphocytes specific for different virus antigens [23,24]. These observations, explained by the molecular structure of class I HLA antigens [25] suggest that our findings are due to a different ability for antigen presentation by B51 + and B52+ lymphocytes.…”
Section: Discussioncontrasting
confidence: 38%
“…These two mutations had no effect on allorecognition; nor did they affect recognition of two distinct influenza virus peptides by appropriate clones (24,25). (ii) Residues on the sides ofthe helices facing into the site (residues 63, 66, 70, 74, 77, 80, 152, and 156).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, changes in the two residues examined that are outside of the groove, residues 43 and 107, did not affect recognition, whereas each of the other mutations had an effect on at least one CTL clone. These mutations include residue 9 (which points upward into the site from a P3 strand on the floor) and residue 70 (which points inward from the a1-helix and interacts with residue 9), as well as residue 74, which had no effect in one virus peptide-specific MHC-restricted CTL recognition study (24) but drastically affected another (25). (iv) The most profound effect was found with mutations at both residues 62 and 63; all CTL examined failed to recognize this mutant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each mutation results in a unique pattern of stimulation of the T-cell clones, and each DR3-restricted T cell clone is stimulated by a different subset of the mutants. This complex relationship of fine structure to antigen-presenting function has been a consistent finding among the murine and human MHC class I and class II molecules examined to date (8,(30)(31)(32)(33)(34)(35)(36)(37) (Table 2). A direct role in antigen presentation for position 74 is consistent with the predicted functional importance of polymorphic residues.…”
Section: Discussionmentioning
confidence: 89%